A Symbian-based mobile solution for intra-body temperature monitoring - Pereira, Orlando R. E. (2012)
Copyright © [2010] IEEE. Reprinted from 12th IEEE International Conference on e-Health Networking, Applications and Services . ISBN: 978-1-4244-6374-9. This material is posted here with permission of the IEEE. Internal or personal use of this material is permitted. However, permission to reprint/republish this material for advertising or promotional purposes or for creating new collective works for resale or redistribution must be obtained from the IEEE by writing to pubs-permissions@ieee.org. By choosing to view this document, you agree to all provisions of the copyright laws protecting it.”